(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The surrogate motherhood, widespread in some States of the U.S.A., Asia and continental Europe, is a reproduction practice prohibited in Italy, according to the article 12, paragraph n. 6, of the Italian Law n. 40/2004 about the artificial procreation. The present paper – after a brief recognition of the italian and european case-law – tries to respond to the principal legal questions deriving from the violation of the domestic prohibition, realized into the national territory or abroad, particularly in relation to the effects of surrogacy contract and in order to the correct institution of parental relationship with the newborn baby.